Constraints on electroweak contact interactions from LEP and tevatron data - Belyaev, Alexander [UNESP]; Rosenfeld, Rogério [UNESP] (World Scientific Publishing, 1999)
A complete set of dimension-six effective contact interactions involving Higgs, gauge bosons and quarks is studied. Limits on the coefficients of these new operators are obtained from the experimental values of the Z and W gauge bosons widths.